2019
DOI: 10.1002/cam4.2233
|View full text |Cite
|
Sign up to set email alerts
|

Toward automatic prediction of EGFR mutation status in pulmonary adenocarcinoma with 3D deep learning

Abstract: To develop a deep learning system based on 3D convolutional neural networks (CNNs), and to automatically predict EGFR‐mutant pulmonary adenocarcinoma in CT images. A dataset of 579 nodules with EGFR mutation status labels of mutant (Mut) or wild‐type (WT) was retrospectively analyzed. A deep learning system, namely 3D DenseNets, was developed to process 3D patches of nodules from CT data, and learn strong representations with supervised end‐to‐end training. The 3D DenseNets were trained with a training subset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
77
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 42 publications
3
77
3
Order By: Relevance
“…Also, another work based on deep learning techniques with an interpretable visual output, identified that the regions surrounding the nodule were the most relevant for the classification decision 31,44 . In our opinion, it is crucial to emphasise this characteristic, as it might change the direction and broaden the analysis spectrum of future radiogenomics studies, which until now have been mainly focusing on the nodule or in a region of interest (ROI) around it 16,45,46 . Lung cancer is the result of multiple and complex combinations of morphological, molecular and genetic alterations 47 .…”
Section: Discussion and Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, another work based on deep learning techniques with an interpretable visual output, identified that the regions surrounding the nodule were the most relevant for the classification decision 31,44 . In our opinion, it is crucial to emphasise this characteristic, as it might change the direction and broaden the analysis spectrum of future radiogenomics studies, which until now have been mainly focusing on the nodule or in a region of interest (ROI) around it 16,45,46 . Lung cancer is the result of multiple and complex combinations of morphological, molecular and genetic alterations 47 .…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…biomarkers, decreasing multiple undesirable side effects associated with cancer treatment 15 . Several clinical trials have been performed to evaluate the efficacy and safety of treatments for lung cancer patients with EGFR mutations 16 . EGFR is a receptor tyrosine kinase that controls the growth and proliferation of cells.…”
mentioning
confidence: 99%
“…The AI diagnosis system used in the study was supported and maintained by Diannei Technology Co. Ltd (Shanghai, China). The core diagnosis component of the AI system was 3D DenseSharp Network, a state‐of‐the‐art multitask learning deep neural network based on 3D DenseNets, with classification and segmentation heads for diagnosing and segmenting lung nodules. In the primary study on cross‐modal pathological invasiveness prediction from CT scans, the software developer set up a single‐cohort data set, which involved 651 patients from Huadong Hospital affiliated to Fudan University, Shanghai, China .…”
Section: Methodsmentioning
confidence: 99%
“…Based on this data set, the 3D DenseSharp Network was developed to train and predict the invasiveness labels and lesion segmentation, with a superior performance over radiologists on this task. The AI system used in this study, developed with the 3D deep learning technology, took advantage of a multicohort data set, with 10x more patients than their primary study . Using this AI system, dicom files were analyzed to screen out intrapulmonary subsolid nodules and their three‐dimensional (3D) volumes, radial lines, probability of nodules and malignancy, probable pathological patterns and other parameters.…”
Section: Methodsmentioning
confidence: 99%
“…Medical imaging has been playing an increasing key role in personalized precision medicine. Radiomics has been applied to oncology studies (13) and has been widely used in diagnosis (14), prognostic evaluation (15), prediction of biological behaviors (16), and even genetic prediction (11,17).…”
mentioning
confidence: 99%